The Importance of Needs Analysis in Curriculum Development Language Learning - Irfadila, Mimi Sri; Noprika, Winda (Proceeding of International Conference on Language Pedagogy (ICOLP), 2022)
Curriculum development is needed to perfect the achievement of educational goals. Curriculum development involves several parties, starting from the government to educators or teachers. However, the phenomenon that occurs shows that curriculum development seems to only follow the dynamics of government policies and the recent Covid situation. This resulted in curriculum development not achieving educational goals. This article aims to discuss needs analysis as a basic reference before carrying out curriculum development. This article also aims to describe the views and stages in carrying out a needs analysis to develop a curriculum in language learning. The method of writing this article uses a literature study technique by presenting theories from experts and reviewing research results related to the needs analysis of curriculum components. Data analysis was carried out by means of data reduction, data presentation, and drawing conclusions. The results of this study will explain that before carrying out curriculum development it is necessary to carry out a needs analysis so that every aspect that is improved achieves educational goals.